Oil Extraction and Human Mobility in Western Uganda: A Case Study of Masindi District. - Mugabi, Ivan (Kabale University, 2025)
A range of policies aimed at mitigating the impacts of oil extraction on the environment and local communities have been developed. However, these policies are more needed to address human mobility and better prevent the practical and psychological impacts on those displaced by oil extraction activities. Human mobility should be integrated into relevant environmental and climate change policies to support communities in areas like the Masindi district.